Graft-versus-host disease affecting oral cavity. A review - Margaix-Muñoz, Maria (J Clin Exp Dent, 2015)
Graft versus host disease (GVHD) is one of the most frequent and serious complications of hematopoietic stem cell transplantation, and is regarded as the leading cause of late mortality unrelated to the underlying malignant disease. GVHD is an autoimmune and alloimmune disorder that usually affects multiple organs and tissues, and exhibits a variable clinical course. It can manifest in either acute or chronic form. The acute presentation of GVHD is potentially fatal and typically affects the skin, gastrointestinal tract and liver. The chronic form is characterized by the involvement of a number of organs, including the oral cavity. Indeed, the oral cavity may be the only affected location in chronic GVHD. The clinical manifestations of chronic oral GVHD comprise lichenoid lesions, hyperkeratotic plaques and limited oral aperture secondary to sclerosis. The oral condition is usually mild, though moderate to severe erosive and ulcerated lesions may also be seen. The diagnosis is established from the clinical characteristics, though confirmation through biopsy study is sometimes needed. Local corticosteroids are the treatment of choice, offering overall response rates of close to 50%. Extracorporeal photopheresis and systemic corticosteroids in turn constitute second line treatment. Oral chronic GVHD is not considered a determinant factor for patient survival, which is close to 52% five years after diagnosis of the condition. Key words:Chronic graft-versus-host disease, oral chronic graft-versus-host disease, pathogenics, management, survival.